Membaca Ulang Makna Filantropi Islam Menurut Pandangan Nahdlatul Ulama Dan Muhamadiyah : Membaca Ulang Makna Filantropi Islam Menurut Pandangan Nahdlatul Ulama Dan Muhamadiyah - Ahmad Rezy Meidina; Mega Puspita ‎; Mohd Hafizi bin Tajuddin (el-Uqud: Jurnal Kajian Hukum Ekonomi Syariah, 2023)
Writing This asks about Islamic philanthropy because There is a shifting meaning of philanthropy in the past. Experts state that philanthropy is an element important in Islam. in between forms of philanthropy in Islam is zakat which is Wrong and One of the five pillars of Islam. in between form other Islamic philanthropy is infaq, alms, and waqf. Therefore philanthropy has a position main in life Muslims. meaning above different from known philanthropy on public now, however No reduce substance from philanthropy That alone. Writing This aim To give understanding to the public generally about shift meaning of Islamic philanthropy, and the necessary exists revitalization meaning of Islamic philanthropy through the view of Nahdlatul Cleric And Muhammadiyah as a primary data source. Findings in the study This that Muhammadiyah's role is important in changing Islamic philanthropy in Indonesia with various activity generosity made from traditional practice become more organized. Meanwhile, Nahdlatul Clerics on the contrary No agree with the practice of generosity made by Muhammadiyah, This was caused Because of thinking of the tradition with by to sect syafi'i.